Sequential Entry of Transforming Markers into Neisseria meningitidis After Chromosome Alignment - Jyssum, Kaare (1969)
The kinetics of appearance of transformants as a function of time of exposure to deoxyribonucleic acid (DNA) was examined in Neisseria meningitidis. Incubation with chloramphenicol for as long as 2 hr, which probably leads to chromosome alignment, resulted in augmentation of the lag period before the appearance of the first transformants. The lag periods thus found were dependent upon the marker tested. This permitted the construction of a time map according to the lag periods observed for individual markers. This map was in general agreement with the chromosome map of the recipient strain as determined by marker frequency analysis. Transformation of recipient cells with chromosomes aligned by growth to the stationary phase showed the same type of increased lag in the appearance of transformants before the logarithmic phase of growth had again been reached. These results support the assumption that the nature of the marker accepted by a recipient cell corresponds to the marker present at the replication point of the chromosome. In the absence of DNA and protein synthesis, the uptake of one marker seems to be successively followed by other markers in a linear order determined by the chromosome of the recipient cell.